Remittances and financial openness - Michel Beine; Elisabetta Lodigiani; Robert Vermeulen (Center for Economic Studies and ifo Institute (CESifo), 2010)
Remittances have greatly increased during recent years, becoming an important and reliable source of funds for many developing countries. Therefore, there is a strong incentive for receiving countries to attract more remittances, especially through formal channels that turn to be either less expensive or less risky. One way of doing so is to increase their financial openness, but this policy option might generate additional costs in terms of macroeconomic volatility. In this paper we investigate the link between remittance receipts and financial openness. We develop a small model and statistically test for the existence of such a relationship with a sample of 66 mostly developing countries from 1980-2005. Empirically we use a dynamic generalized ordered logit model to deal with the categorical nature of the financial openness policy. We apply a two-step method akin to two stage least squares to deal with the endogeneity of remittances and potential measurement errors. We find a strong positive statistical and economic effect of remittances on financial openness.
Keywords: E60; F24; F41; O10; 330; remittances; financial openness; government policy; Rücküberweisung (Migranten); Kapitalmarktliberalisierung; Offene Volkswirtschaft; Makroökonomischer Einfluss; EU-Staaten; Schwellenländer